DNA barcoding confirms the presence of Hydria cervinalis (Scopoli, 1763) in the Iberian Peninsula (Lepidoptera: Geometridae: Larentiinae) - Rubio, Rosa M.; Guerrero, Juan J.; Garre, Manuel; Ortiz, Antonio S. (Zootaxa, 2013)
The genus Hydria Hübner, 1822 is distributed across the Palearctic and Nearctic regions, and includes more than 50 species in South America. In Europe, this genus includes five species subdivided into three species-groups, the undulata, the cervinalis and the montivagata species group (Hausmann & Viidalepp 2012). Of these five species, three have been reported from the Iberian Peninsula, Hydria undulata (Linnaeus 1758), H. gudarica (Dufay 1983), and H. montivagata andalusica (Ribbe 1912) (Redondo et al. 2009; Hausmann & Viidalepp 2012). Hydria cervinalis (Scopoli, 1763) is widely distributed from England to western European Russia to the east and from southern Fennoscandia, to the Alps and Carpathians Mountains in the south. This distribution matches a Euro-Caucasian pattern (Hausmann & Viidalepp 2012). H. cervinalis was cited from Eastern Pyrenees (Mazel & Peslier 1997), in the southern Iberian System based on one female from Uña (Cuenca) (Dominguez 1991, unpublished) and from Albarracin (Teruel) (Zerny 1927). However, according to Redondo et al. (2009), all these records must be referred to H. gudarica. Recently, H. cervinalis has been cited by Hausmann and Viidalepp (2012) in the Iberian Peninsula based on our data.